Ferrite powder and method of manufacturing the same

A ferrite powder with controlled iron, manganese, and α-Fe2O3 content, manufactured through specific processes, addresses the low electrical resistance issue of spherical ferrite powders, maintaining high dielectric strength and magnetic properties in resin compositions.

KR103042889B1Active Publication Date: 2026-11-03POWDERTECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020227025147
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-27
Filing Date
2021-01-27
Publication Date
2026-11-03
Estimated Expiration
2041-01-27

AI Technical Summary

Technical Problem

Ferrite powder consisting of spherical particles produced by thermal spraying has low electrical resistance, leading to decreased breakdown voltage when mixed with resin, particularly at high filling rates, causing insulation breakdown in resin compositions.

Method used

A ferrite powder composition with specific ranges of iron (Fe), manganese (Mn), and α-Fe2O3 content, along with controlled particle size and shape, is manufactured through a process involving raw material mixing, pre-sintering, crushing, granulating, and thermal spraying, to enhance electrical resistance and maintain high magnetic properties.

Benefits of technology

The resulting ferrite powder maintains high dielectric strength and magnetic properties even at high filling rates in resin compositions, preventing insulation breakdown and ensuring excellent moldability and filling properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112022075442954-PCT00001
    Figure 112022075442954-PCT00001
  • Figure 112022075442954-PCT00002
    Figure 112022075442954-PCT00002
  • Figure 112022075442954-PCT00003
    Figure 112022075442954-PCT00003
Patent Text Reader

Abstract

The present invention relates to a ferrite powder and a method for manufacturing the same, which can maintain a high dielectric strength even when applied to a resin composition with a high filling rate due to high magnetic properties and electrical resistance. The ferrite powder is composed of spherical ferrite particles, wherein the ferrite powder contains 55.0 to 70.0 mass% of iron (Fe) and 3.5 to 18.5 mass% of manganese (Mn), the amount of α-Fe2O3 is greater than 0.0 mass% and less than or equal to 7.5 mass%, and the volume average particle diameter (D50) of the ferrite powder is 15.0 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to ferrite powder and a method for manufacturing the same. Background Technology

[0002] Ferrite-resin composite materials (resin compositions) consisting of ferrite powder and resin are used for various applications, including electromagnetic shielding materials. These composite materials are produced by mixing ferrite powder with resin using ferrite powder as a filler, and are molded into shapes such as sheets to form a molded body (composite). At this time, if the shape of the particles constituting the ferrite powder is close to spherical, the fluidity during molding increases, and the filling rate of the ferrite powder within the composite increases. Consequently, not only is the moldability improved, but characteristics such as electromagnetic shielding performance are also excellent. From this perspective, ferrite powder composed of spherical particles has been conceived, and it has been proposed to produce such spherical particles using the thermal spraying method.

[0003] For example, Patent Document 1 (International Publication No. 2017 / 212997) discloses ferrite particles having a single crystal with an average particle size of 1 to 2000 nm and a spherical particle shape, wherein the ferrite particles substantially do not contain Zn, contain 3 to 25 wt% of Mn and 43 to 65 wt% of Fe, and the real part (μ') of the complex permeability measured by a molded body made of the ferrite particles and a binder resin has a maximum value in the frequency band of 100 MHz to 1 GHz (Claim 1 of Patent Document 1). In addition, Patent Document 1 describes that a granulated product made of ferrite raw material is manufactured by spraying it in the atmosphere to ferrite it, then rapidly cooling and solidifying it, and subsequently recovering only the particles with a particle size within a predetermined range, and that when used as an electromagnetic shielding material for electronic devices, it can stably shield electromagnetic waves in a wide frequency band requiring shielding regardless of frequency (Patent Document 1

[0039] and

[0078] ).

[0004] Patent Document 2 (International Publication No. 2017 / 169316) describes Mn-based ferrite particles having a spherical particle shape and a single crystal with an average particle size of 1 to 2000 nm, wherein the saturation magnetization is 45 to 95 Am 2 Ferrite particles characterized by having a weight of / kg are disclosed (Claim 1 of Patent Document 2). In addition, Patent Document 2 describes that a ferrite raw material containing Mn and Fe is ferrite-ized by spraying it in the atmosphere, and then rapidly cooling and solidifying it, and subsequently recovering only the particles with a particle size within a predetermined range, thereby producing a high saturation magnetization and excellent dispersibility in a resin, solvent, or resin composition (

[0033] and

[0089] of Patent Document 2).

[0005] Patent document 3 (Japanese Patent Publication No. 2016-060682) discloses a spherical ferrite powder characterized by containing 15 to 30 weight% of ferrite particles with a particle size of less than 11 μm and having a volume average particle size of 10 to 50 μm. It is described that the adjusted aggregates are ferrite-formed by thermal spraying in the atmosphere, and that when used as a filler, the filling and moldability are good, and the molded body has excellent handling properties and high resistance. Therefore, the spherical ferrite powder can be formed into a resin composition with a resin and molded to be used for various purposes, including sealants for ICs for electromagnetic wave absorption (Claim 1 of Patent document 3,

[0058] and

[0093] ).

[0006] Patent document 4 (Japanese Patent Publication No. 2005-015303) discloses a method for manufacturing spherical powder, characterized by comprising: a surface treatment process in which a raw material powder and a treatment agent comprising at least one of a higher fatty acid or its derivative, a higher hydrocarbon, and a higher alcohol are heated to a predetermined temperature and then stirred to surface treat the raw material powder; and a spherical powder generation process in which the surface-treated raw material powder is introduced into a combustion flame generated from a burner to melt and spheroidize it, and the raw material powder is solidified by moving out of the combustion flame to obtain the spherical powder (Claim 1 of Patent Document 4). Prior art literature

[0007] Patent Document 1: International Publication No. 2017 / 212997 Patent Document 2: International Publication No. 2017 / 169316 Patent Document 3: Japanese Patent Publication No. 2016-060682 Patent Document 4: Japanese Patent Publication No. 2005-015303 The problem to be solved

[0008] However, the inventors found that ferrite powder consisting of spherical particles produced by thermal spraying has low electrical resistance, and that when this is mixed with resin to form a resin composition, it may cause problems in terms of breakdown voltage. In particular, when the filling rate of the ferrite powder is high, the breakdown voltage of the resin composition decreases. If the breakdown voltage of the resin composition is low, the resin composition undergoes insulation breakdown when voltage is applied, which becomes a problem as a device.

[0009] As a result of further investigation by the inventors, it was found that in a ferrite powder composed of spherical particles, by including a predetermined amount of α-Fe2O3, the electrical resistance can be increased while maintaining high magnetic properties (saturation magnetization, permeability) of the ferrite powder, and that when this ferrite powder is applied to a resin composition, a high dielectric strength can be maintained even with a high filling rate.

[0010] The present invention is completed based on such findings and aims to provide a ferrite powder and a method for manufacturing the same, which has high magnetic properties and electrical resistance and can maintain a high withstand voltage even when applied to a resin composition with a high fill rate. means of solving the problem

[0011] The present invention includes the forms (1) to (7) below. Meanwhile, in this specification, the expression '~' includes the numerical values ​​at both ends. That is, 'X~Y' means 'X or greater and Y or less'.

[0012] (1) A ferrite powder composed of spherical ferrite particles,

[0013] The ferrite powder contains 55.0 to 70.0 mass% iron (Fe) and 3.5 to 18.5 mass% manganese (Mn), and the amount of α-Fe2O3 is greater than 0.0 mass% and less than or equal to 7.5 mass%, and

[0014] Ferrite powder having a volume average particle diameter (D50) of 15.0 μm or less.

[0015] (2) Ferrite powder described in (1), wherein the amount of α-Fe2O3 is 3.0 mass% or more and 6.0 mass% or less.

[0016] (3) Ferrite powder described in (1) or (2), having a volume average particle diameter (D50) of 2.0 μm or more.

[0017] (4) Ferrite powder described in any one of (1) to (3), wherein the average shape factor SF-1 of the ferrite powder is 100 to 110.

[0018] (5) Ferrite powder described in any one of (1) to (4), wherein the carbon (C) content of the ferrite powder is 0.12 mass% or less.

[0019] (6) The volume resistivity of the ferrite powder is 1.0×10 8 Ferrite powder described in any one of (1) to (5) above, having a value of Ω·cm or more.

[0020] (7) A method for manufacturing ferrite powder as described in any one of (1) to (6) above, comprising the following process:

[0021] A process of producing a raw material mixture by mixing ferrite raw materials,

[0022] A process of making a plastic product by pre-sintering the above raw material mixture,

[0023] A process of crushing and granulating the above-mentioned plastic material to form an aggregate, and

[0024] The above assembly has a process of thermal spraying to make a thermal spray product,

[0025] A method having the carbon content of the above assembly 0.001 to 0.095 mass%, and in the thermal spraying process, a raw material supply rate of 2.5 to 9.0 kg / hour, a combustion gas flow rate of 3 to 10 m³ / hour, and an oxygen flow rate of 18 to 60 m³ / hour. Effects of the invention

[0026] According to the present invention, a ferrite powder having high magnetic properties and electrical resistance, capable of maintaining a high dielectric strength even when applied to a resin composition with a high filling rate, and a method for manufacturing the same are provided. Specific details for implementing the invention

[0027] Specific embodiments of the present invention (hereinafter referred to as "the present embodiments") will be described. Meanwhile, the present invention is not limited to the following embodiments, and various modifications are possible within the scope of not altering the gist of the present invention.

[0028] 1. Ferrite powder

[0029] The ferrite powder of the present embodiment consists of spherical ferrite particles. That is, the ferrite powder contains a number of spherical ferrite particles. By being composed of spherical ferrite particles, the ferrite powder can be made to have excellent moldability and filling properties when applied as a filler to a resin composition (ferrite resin composite material). Spherical particles smoothly avoid contact with other particles when in contact during molding. For this reason, not only is the fluidity during molding good, but the particles are also densely filled. In contrast, particles having an anisotropic shape (irregular shape), such as plate-like or needle-like, have poor moldability and filling properties. Meanwhile, in this specification, irregularly shaped particles include anisotropic shaped particles and are used in contrast to regular shaped particles such as spherical particles.

[0030] The ferrite powder of the present embodiment contains 55.0 to 70.0 mass% of iron (Fe) and 3.5 to 18.5 mass% of manganese (Mn). The ferrite powder has a composition of manganese (Mn) ferrite. In manganese (Mn) ferrite, if the iron (Fe) content is excessively low or the manganese (Mn) content is excessively high, the saturation magnetization (σs) decreases, or the imaginary part of the permeability (μ'') and the loss factor (tanδ) increase. Therefore, when the ferrite powder is applied to a resin composition, there is a risk that the saturation magnetic flux density will decrease or magnetic loss will increase. On the other hand, if the iron (Fe) content is excessively high or the manganese (Mn) content is excessively low, the ferrite composition approaches magnetite. Magnetite (FeO·Fe2O3) is unstable divalent iron ions (Fe 2+ Because it contains ), there is a concern that the saturation magnetization (σs) may decrease due to oxidation. In this regard, the iron (Fe) and manganese (Mn) content of the ferrite powder is limited to the aforementioned range. The ferrite powder may contain 57.0 to 70.0 mass% of iron (Fe) and 4.5 to 15.0 mass% of manganese (Mn), or 58.0 to 69.0 mass% of iron (Fe) and 6.0 to 10.0 mass% of manganese (Mn). The total of iron (Fe) and manganese (Mn) does not exceed 73.0 weight%.

[0031] Ferrite is an oxide. Therefore, the ferrite powder contains oxygen (O) in addition to iron (Fe) and manganese (Mn). Furthermore, as long as the aforementioned compositional range is satisfied, it may contain other components other than iron (Fe), manganese (Mn), and oxygen (O). Examples of such components include zinc (Zn), magnesium (Mg), strontium (Sr), titanium (Ti), lithium (Li), barium (Ba), yttrium (Y), nickel (Ni), copper (Cu), and cobalt (Co). However, from the perspective of fully exhibiting the characteristics of manganese (Mn) ferrite, the content of other components is preferably 1.0 mass% or less, and more preferably 0.5 mass% or less. The ferrite powder may contain iron (Fe), manganese (Mn), and oxygen (O), and the remainder may have a composition of unavoidable impurities. Here, unavoidable impurities refer to components that are inevitably incorporated during the manufacturing process, and the content thereof is 5000 ppm or less. Unavoidable impurities include silicon (Si), aluminum (Al), calcium (Ca), chlorine (Cl), boron (B), zirconium (Zr), and chromium (Cr).

[0032] The ferrite powder of the present embodiment contains an amount of α-Fe2O3 greater than 0.0 mass% and less than or equal to 7.5 mass%. By incorporating α-Fe2O3 (hematite), the decrease in electrical resistance and withstand voltage can be suppressed while maintaining the high magnetic properties of the ferrite powder. The reason for this is as follows. During manufacturing, the iron (Fe) component, which is the raw material, reacts with a transition metal component such as manganese (Mn) to form ferrite components such as the spinel phase, which is a ferromagnetic material. The spinel phase is a complex oxide containing divalent and trivalent metal ions, such as manganese ferrite ((Mn,Fe)O·(Mn,Fe)2O3) or magnetite (FeO·Fe2O3). Here, the manganese (Mn) ions and iron (Fe) ions can assume either divalent or trivalent valence. Because of this, an electron hopping phenomenon occurs within the spinel phase, and electrical conduction occurs. Accordingly, ferrites consisting solely of the spinel phase, particularly manganese (Mn) ferrites, tend to have lower electrical resistance.

[0033] In this regard, α-Fe2O3 (hematite) is free iron oxide derived from iron (Fe) components that did not form a spinel phase. α-Fe2O3 consists of trivalent iron ions (Fe 3+ It contains ), but divalent iron ions (Fe 2+It does not contain α-Fe2O3. For this reason, it is a stable compound with high electrical resistance. Therefore, when the spherical ferrite particles in the ferrite powder contain α-Fe2O3, the conductive path through the spinel phase is severed, and the electrical resistance and withstand voltage increase. For this reason, α-Fe2O3 is an essential component, that is, the amount of α-Fe2O3 is limited to more than 0.0 mass%. The amount of α-Fe2O3 can be 0.1 mass% or more, 0.5 mass% or more, 1.0 mass% or more, 2.0 mass% or more, 3.0 mass% or more, or 4.0 mass% or more. On the other hand, unlike the spinel phase, α-Fe2O3 is a paramagnetic material. For this reason, if the amount of α-Fe2O3 is excessively high, there is a risk that the magnetic properties (saturation magnetization, permeability) of the ferrite powder will deteriorate. The amount of α-Fe2O3 can be 7.0 mass% or less, or 6.0 mass% or less.

[0034] Ferrite powder (spherical ferrite particles) contains mainly a spinel phase in addition to α-Fe2O3. The content of the spinel phase may be 80 mass% or more, 85 mass% or more, 90 mass% or more, or 95 mass% or more. Furthermore, the ferrite powder may contain other phases or unavoidable impurities other than the spinel phase and α-Fe2O3. Examples of such phases include excess manganese oxides (MnO, Mn2O3, Mn3O4, etc.) or iron oxides other than spinel (γ-Fe2O3, FeO, Mn3FeO8, etc.). However, the ferrite powder does not need to contain other phases. That is, the ferrite powder may contain the spinel phase and α-Fe2O3, with the remainder being unavoidable impurities. Meanwhile, as previously mentioned, the unavoidable impurities are components with a content of 5000 ppm or less. In addition, the ferrite powder of the present embodiment contains α-Fe2O3 in the spherical ferrite particles constituting it. For example, α-Fe2O3 may be dispersed inside the spherical ferrite particles. Accordingly, this ferrite powder is distinguished from a mixture of α-Fe2O3-non-containing ferrite particles and α-Fe2O3.

[0035] The ferrite powder of the present embodiment has a volume average particle diameter (D50) of 15.0 μm or less. If D50 exceeds 15.0 μm, there is a problem in that the loss factor (tanδ) becomes too large and the dielectric strength decreases. D50 may be 10.0 μm or less, or 7.0 μm or less. The lower limit of D50 is not specifically limited. However, by making D50 larger to some extent, the increase in viscosity of the resin composition is suppressed, and the filler filling rate can be increased. D50 may be 2.0 μm or more, or 2.5 μm or more. The particle size distribution may have two or more peaks. Here, having two or more peaks means having two or more points (maximum points, inflection points, saddle points, etc.) where the derivative (derivative coefficient) of the function or the derivative is zero when viewed as a function of particle size, when viewed as a function of particle size (provided that the particle size is expressed in logarithmic notation).

[0036] The ferrite powder preferably has an average shape factor SF-1 of 100 to 110. SF-1 is an indicator of the sphericity of the particles (powder), which is 100 for a perfect sphere and increases as it deviates from a sphere. By making SF-1 110 or less, the fluidity of the powder is increased, resulting in superior moldability and fillability. SF-1 may be 108 or less, 105 or less, or 103 or less.

[0037] Meanwhile, the average shape factor SF-1 of the ferrite powder is obtained by determining the shape factor SF-1 of each particle for a plurality of ferrite particles and calculating the average value. The SF-1 of the ferrite particle is determined by the horizontal ferret's diameter R (unit: μm), projected perimeter L (unit: μm), and projected area S (unit: μm) of the particle. 2 ) can be measured and obtained by the following formula (1).

[0038]

[0039] Preferably, the ferrite powder has a BET specific surface area of ​​0.01 to 3.00 m² / g. By keeping the BET specific surface area at 3.00 m² / g or less, aggregation of the ferrite powder can be suppressed, resulting in better moldability and fillability. On the other hand, by keeping the BET specific surface area at 0.01 m² / g or more, the occurrence of inter-particle voids can be suppressed, resulting in better fillability. Furthermore, by keeping the BET specific surface area within the above range, adhesion to the resin is improved when the ferrite powder is applied to a composite material or composite. The BET specific surface area may be 0.10 to 2.00 m² / g.

[0040] The ferrite powder preferably has a tap density of 0.50 to 5.00 g / cm³. The tap density can be increased by mixing fine particles and large particles, and as a result, the packing properties of the ferrite powder become better overall. The tap density may be 1.50 to 3.50 g / cm³.

[0041] The ferrite powder preferably has a carbon (C) content of 0.12 mass% or less. This carbon is a component derived mainly from residual carbon (C) compounds originating from organic components (dispersants, binder resins, etc.) added during the manufacture of ferrite powder. If the amount of organic components added during the manufacture of ferrite powder is too small, the supply of raw materials during thermal spraying becomes unstable, making it easy for irregularly shaped particles to be incorporated into the ferrite powder. Irregularly shaped particles cause deterioration of magnetic properties and packing properties. For this reason, it is desirable for the ferrite powder to contain a certain amount of carbon. The amount of carbon (C) should be 0.001 mass% or more, 0.002 mass% or more, or 0.003 mass% or more. On the other hand, if the carbon (C) content is excessively high, there is a risk that the curing of the resin may be inhibited when the ferrite powder is applied to a resin composition as a filler. Although the detailed mechanism is unclear, it is suspected that residual carbon (C) compounds derived from organic components are straight-chain compounds that do not have functional groups, and that they react with the resin and have an adverse effect on curing. The carbon content may be 0.100 mass% or less, 0.080 mass% or less, 0.050 mass% or less, or 0.010 mass% or less.

[0042] The ferrite powder is preferably erucic acid amide (C) as a residual carbon (C) compound. 22 H 43 NO), butyl palmitate (C 20 H 40 O2) and butyl stearate (C 22 H 44 It contains one or more compounds selected from the group consisting of O2). These compounds mainly consist of components derived from organic components (dispersants, binder resins, etc.) added during the manufacture of ferrite powder. If organic components are not added during the manufacture of ferrite powder, not only will the magnetic properties of the ferrite powder be degraded, but the fillability of the resin composition may also be poor.

[0043] The ferrite powder of the present embodiment has high electrical resistance because it contains α-Fe2O3. The volume resistivity of the ferrite powder is 1.0 × 10⁻⁶. 8 It must be Ω·cm or greater, and 2.0×10⁻⁶ 8 It must be Ω·cm or greater, and 4.0×10⁻⁶ 8 It may be Ω·cm or greater. The upper limit of the volume resistivity is not specifically limited, but 1.0×10⁻⁶ 10 Ω·cm or less is typical.

[0044] Ferrite powder can be used as a filler and mixed with resin to form a resin composition for applications such as electromagnetic shielding materials. Here, the electrical resistance of the resin, α-Fe2O3-containing ferrite powder, and α-Fe2O3-free ferrite powder is lower in this order. That is, the electrical resistance of the resin is the highest, and the electrical resistance of the α-Fe2O3-free ferrite powder is the lowest. Furthermore, as the filling rate of ferrite powder in the resin composition increases, not only does the distance between ferrite powders shorten, but some of the ferrite powders also come into contact with each other. For this reason, if α-Fe2O3-free ferrite powder with low electrical resistance is used as a filler in a high-filling-rate resin composition, the withstand voltage decreases. This is because when voltage is applied, a conductive path is formed between the ferrite particles with low electrical resistance, causing breakdown (insulation breakdown). In contrast, if α-Fe2O3-containing ferrite powder with high electrical resistance is used as a filler, such a decrease in withstand voltage can be prevented.

[0045] In addition, since the amount of paramagnetic α-Fe2O3 and the volume average particle diameter (D50) of the ferrite powder of the present embodiment are limited, not only are high magnetic properties (saturation magnetization, permeability) maintained, but the loss factor (tanδ) can also be suppressed to a low level. For this reason, the magnetic properties of the resin composition can be made excellent. The saturation magnetization (σs) of the ferrite powder may be 65 emu / g or higher, 70 emu / g or higher, 75 emu / g or higher, 80 emu / g or higher, or 85 emu / g or higher. The upper limit of the saturation magnetization (σs) is not particularly limited, but is typically 95 emu / g or lower. In addition, the tanδ of the ferrite powder at 100 MHz may be 0.20 or lower, 0.13 or lower, or 0.06 or lower. The lower limit of tanδ is not specifically limited, but is typically greater than or equal to 0.001.

[0046] 2. Method for manufacturing ferrite powder

[0047] The method for manufacturing ferrite powder according to the present embodiment comprises the following processes: a process of mixing ferrite raw materials to produce a raw material mixture (raw material mixing process); a process of pre-sintering the obtained raw material mixture to form a sintered product (sintering process); a process of crushing and granulating the obtained sintered product to form a granulated product (granulation process); and a process of spraying the obtained granulated product to form a sprayed product (spraying process). In addition, the carbon content of the granulated product is set to 0.001 to 0.095 mass%, and in the spraying process, the supply rate of the spraying raw material is set to 2.5 to 9.0 kg / hour, the combustion gas flow rate to 3 to 10 m³ / hour, and the oxygen flow rate to 18 to 60 m³ / hour. Details of each process are described below.

[0048] <Raw Material Mixing Process>

[0049] A raw material mixture is prepared by mixing ferrite raw materials. As the ferrite raw materials, known ferrite raw materials such as oxides, carbonates, hydroxides, and / or chlorides may be used. For example, as iron (Fe) and manganese (Mn) raw materials, iron oxide (Fe2O3), trimanganese tetroxide (Mn3O4), and / or manganese dioxide (MnO2) may be used. The mixing ratio of the raw materials should be such that a ferrite powder of the desired composition is obtained. The mixing of the raw materials may be carried out using a known mixer such as a Henschel mixer, and may be performed in either a dry or wet manner, or both. Additionally, the raw material mixture may be compacted (pre-compacted) using an compaction device such as a roller compactor.

[0050] <Plasticity Process>

[0051] In the plasticization process, the obtained raw material mixture is plasticized to form a plasticized product. Plasticization can be carried out by known methods. For example, it can be carried out using a furnace such as a rotary kiln, a continuous furnace, or a batch furnace. The plasticization conditions can also be known conditions. For example, conditions such as maintaining at 700 to 1300°C for 0.5 to 12 hours under an atmosphere such as air can be cited.

[0052] <Assembly Process>

[0053] In the assembly process, the obtained plastic material is crushed and aggregated (main assembly) to form an aggregate (main assembly). The crushing method is not particularly limited. For example, it may be carried out using a known crusher such as a vibratory mill, ball mill, or bead mill, either dry or wet, or both. The assembly method may also be a known method. For example, after crushing, water and, if necessary, additives such as a binder resin such as polyvinyl alcohol (PVA), a dispersant, and / or an antifoaming agent are added to the plastic material to adjust the viscosity, and then the material is aggregated using an aggregater such as a spray dryer.

[0054] In the granulation process, the amount of binder resin and additives added is controlled to adjust the carbon (C) content in the granules to 0.001 to 0.095 mass%. Depending on subsequent thermal spraying conditions, the amount of α-Fe2O3 and carbon (C) in the ferrite powder produced can be controlled by adjusting the amount of carbon (C) in the granules. That is, if the amount of carbon (C) in the granules is high, the amount of carbon (C) in the ferrite powder tends to be high as well. Furthermore, if the amount of carbon (C) is high, the amount of α-Fe2O3 in the ferrite powder tends to be low. This is because the atmosphere during thermal spraying becomes a more reducing atmosphere, making it easier for the ferrite reaction of the granules to proceed. Therefore, if the amount of carbon (C) in the granules is excessively high, there is a risk that α-Fe2O3, which has the effect of suppressing the decrease in electrical resistance, cannot be incorporated into the ferrite powder. The carbon (C) content in the granules may be 0.0750 mass% or less, and may be 0.050 mass% or less. On the other hand, if the amount of carbon (C) in the granules is excessively low, the amount of α-Fe2O3 in the ferrite powder becomes too high, and there is a risk that the magnetic properties will deteriorate. The carbon (C) content in the granules may be 0.005 mass% or more, and may be 0.010 mass% or more.

[0055] <Warrior Process>

[0056] In the thermal spraying process, the granules are sprayed. In thermal spraying, a mixture of combustion gas and oxygen is used as a combustible gas combustion flame source. The granules, which are the raw materials for the thermal spraying, pass through a high-temperature combustion flame. At that time, a ferritization reaction occurs, and simultaneously, a portion of the granules melts to become spherical ferrite particles. In thermal spraying, a mixture of combustion gas and oxygen (total oxygen) can be used as a combustible gas combustion flame source. The volume ratio of combustion gas to oxygen (total oxygen) is preferably 1:3.5 to 1:10.0, and more preferably 1:5 to 1:8.0. Accordingly, it becomes possible to efficiently manufacture spherical ferrite particles. As the combustion gas, combustible gases such as propane gas, propylene gas, and acetylene gas can be used, and among these, propane gas is preferably used.

[0057] In addition, the feed rate of the thermal spray raw material is set to 2.5 to 9.0 kg / hour. If the feed rate (feed amount) is high, spinelification of the granules proceeds, and the amount of α-Fe2O3 in the ferrite powder decreases. This is because a high feed rate increases the amount of fuel in the flame, thereby lowering the flame temperature. When the flame temperature is lowered, the time required for the particles to cool after spraying is shortened, and the generated divalent iron ions (Fe 2+) is prone to remaining within the ferrite particles. In contrast, if the feed rate (feed amount) is low, the formation of α-Fe2O3 is likely to proceed. This is because the amount of raw material in the flame decreases, causing the flame temperature to rise, and as a result, the time required for the particles to cool after thermal spraying becomes longer. By controlling the feed rate in this way, the amount of α-Fe2O3 in the obtained ferrite powder can be adjusted. Furthermore, if the feed rate is excessively high, aggregates tend to adhere to each other, or it becomes difficult to sufficiently carry the ferritization reaction into the interior of the particles. Consequently, there is a risk that spherical particles may not be obtained or that the desired magnetic properties may not be achieved. On the other hand, if the feed rate is excessively low, it causes an increase in manufacturing costs. In this regard, the feed rate of the thermal spray raw material is specified in this embodiment. The feed rate should be 4.0 to 8.0 kg / hour.

[0058] Oxygen used for thermal spraying is also used for the purpose of transporting raw materials to the thermal spraying flame. For this reason, it is divided into combustion oxygen used directly in the flame and raw material supply oxygen that is combusted after transporting the raw materials to the center of the thermal spraying source. The carbon content in the ferrite powder after thermal spraying can be controlled by the volume ratio of combustion oxygen to raw material supply oxygen. It is expressed as 'Total Oxygen = Combustion Oxygen + Raw Material Supply Oxygen', and it is preferable that the volume ratio of combustion oxygen to raw material supply oxygen be 95:5 to 80:20. If the ratio of combustion oxygen becomes larger than the above range (approaching 100), the raw material supply capacity decreases, and there is a possibility that the raw materials may become clogged in the raw material supply piping. If the ratio of combustion oxygen becomes smaller than the above range (below 80), the raw materials are distributed to parts away from the center of the flame where the highest temperature occurs, and the ferritization reaction cannot proceed sufficiently into the interior of the particles, so the amount of α-Fe2O3 contained in the ferrite powder after thermal spraying may increase. In terms of not increasing the amount of α-Fe2O3 more than necessary, it is more desirable that the combustion oxygen:raw material supply oxygen = 95:5 to 85:15, more desirable that the combustion oxygen:raw material supply oxygen = 95:5 to 87:13, and most desirable that the combustion oxygen:raw material supply oxygen = 95:5 to 89:11.

[0059] In addition, it is desirable to set the combustion oxygen to at least 0.85 times the volume required for the complete combustion of the combustion gas. For example, when using propane gas as the combustion gas, it is desirable to have a combustion oxygen volume of at least 4.25 times the volume of the propane gas. By doing so, even if oxygen is supplied in excess of the oxygen required for the complete combustion of the combustion gas, it is possible to prevent the generation of an excessive amount of α-Fe2O3 while minimizing the drop in temperature of the thermal spray flame.

[0060] In addition, it is desirable that the combustion gas ratio be 1.05 or higher and 2.00 or lower. Here, the combustion gas ratio is the ratio of the amount of combustion gas used for actual combustion (N㎥ / hour) to the amount of raw material supplied (kg / hour), and can be calculated by the following equation (2).

[0061]

[0062] The amount of combustion gas used for actual combustion (N㎥ / hour) can be calculated using the following formula (3) or the following formula (4).

[0063]

[0064]

[0065] The particles ferrite-denatured by thermal spraying are rapidly cooled and solidified under an atmospheric environment, and the resulting product is recovered by a cyclone or filter to obtain the thermal spray material.

[0066] <Classification Process>

[0067] If necessary, the obtained thermal spray may be classified. For classification, the particle size can be adjusted to the desired size using known methods such as air classification (airflow classification), mesh classification, or sieve classification. Alternatively, it is possible to separate and recover large and small particles within a single process using airflow classification such as a cyclone. In this way, ferrite powder can be obtained.

[0068] According to the present embodiment, a ferrite powder and a method for manufacturing the same are provided, wherein the composition and the amount of α-Fe2O3 are limited within a predetermined range. This ferrite powder has high magnetic properties and high electrical resistance. For this reason, even when applied to a resin composition with a high filling rate, it can maintain a high withstand voltage.

[0069] 3. Ferrite resin composite material

[0070] The ferrite powder of the present embodiment can be applied to a ferrite resin composite material (resin composition). The ferrite resin composite material contains ferrite powder and resin. By using the ferrite powder of the present embodiment as a filler, a composite material with excellent magnetic properties and withstand voltage can be obtained even with a high filler filling rate.

[0071] Examples of resins constituting the composite material include epoxy resin, urethane resin, acrylic resin, silicone resin, polyamide resin, polyimide resin, polyamideimide resin, fluoropolymer resin, and / or combinations thereof. Here, the silicone resin may be a modified silicone resin modified with acrylic, urethane, epoxy, and / or fluorine.

[0072] The ratio of ferrite powder to the total solid content in the composite material is preferably 50 to 95 mass%, and more preferably 80 to 95 mass%. In addition, the ratio of resin to the total solid content in the composite material is preferably 5 to 50 mass%, and more preferably 5 to 20 mass%. By keeping the ratio of ferrite powder or resin within the above ranges, not only is the dispersion stability of the ferrite powder in the composite material, as well as the storage stability and moldability of the composite material, excellent, but the characteristics such as mechanical strength and electromagnetic shielding performance of the composite (molded body) obtained by molding the composite material are also superior.

[0073] The composite material may contain components other than ferrite powder and resin. Examples of such components include solvents, fillers (organic fillers, inorganic fillers), plasticizers, antioxidants, dispersants, coloring agents, thermally conductive particles, etc.

[0074] Such ferrite resin composite materials can be applied to electromagnetic shielding materials, electronic materials, or electronic components. Electromagnetic shielding materials, electronic materials, or electronic components may be manufactured by molding the composite material using known methods. The molding method is not particularly limited and may include, for example, compression molding, extrusion molding, injection molding, blow molding, or calendering molding. Additionally, it may be a method of forming a film of the composite material on a gaseous phase.

[0075] Example

[0076] The present invention will be explained in more detail using the following examples. However, the present invention is not limited to the following examples.

[0077] (1) Production of ferrite powder

[0078] [Example 1]

[0079] <Raw Material Mixing and Pre-grain Process>

[0080] Iron oxide (Fe2O3) and manganese dioxide (MnO2) were used as raw materials, and the raw materials were weighed and mixed so that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn = 8:1. A Henschel mixer was used for mixing. The obtained mixture was pre-compacted using a roller compactor to produce a pre-compacted product.

[0081] <Plasticity Process>

[0082] A plasticized product was manufactured by plasticizing a pre-coagulated raw material mixture (pre-coagulated product). Plasticization was carried out using a rotary kiln under conditions of 900°C × 1 hour in the atmosphere.

[0083] <Main Assembly Process>

[0084] The obtained plastic material was crushed and granulated to produce a granule (main granule). First, the obtained plastic material was coarsely crushed using a dry bead mill (steel ball beads of 3 / 16 inch φ), water was added, and then finely crushed using a wet bead mill (zirconia beads of 0.65 mm φ). The obtained slurry had a solid content concentration of 50 mass%, and the particle size of the crushed powder (slurry particle size) was 2.367 μm. The viscosity of the slurry was adjusted by adding an ammonium polycarboxylate salt as a dispersant to the obtained slurry at a ratio of 60 cc per 25 kg of solid content in the slurry, and then granulated using a spray dryer. The obtained granule had a volume average particle size of 51.04 μm and a carbon (C) content of 0.0511 mass%.

[0085] <Warrior and Classification Process>

[0086] The obtained aggregate was sprayed and rapidly cooled in a combustible gas combustion flame. During spraying, the ratio of propane gas flow rate to total oxygen flow rate was set to 1:5.42, and the raw material supply rate was set to 1.08 as a ratio of combustion gas flow rate. Subsequently, the cooled particles were recovered by a cyclone installed downstream of the airflow to obtain the sprayed material. From the obtained sprayed material, coarse powder was further removed using a sieve, and fine powder was removed by airflow classification to produce ferrite powder. In the above spraying, the combustion oxygen to raw material supply oxygen ratio was set to 90.8:9.2. Meanwhile, the manufacturing conditions for the ferrite powder are shown in Table 1.

[0087] [Example 2]

[0088] In the main assembly process, an ammonium polycarboxylate salt was added to the slurry at a ratio of 60 cc per 25 kg of solid content in the slurry, and a 10 mass% aqueous solution of polyvinyl alcohol (PVA) was further added as a binder in an amount of 50 cc. Otherwise, ferrite powder was produced in the same manner as in Example 1. The granules obtained in the main assembly process had a volume average particle size of 51.84 μm and a carbon (C) content of 0.0575 mass%.

[0089] [Example 3]

[0090] In the main assembly process, an ammonium polycarboxylate salt was added to the slurry at a ratio of 10 cc per 25 kg of solid content in the slurry, and a 10 mass% aqueous solution of polyvinyl alcohol (PVA) was further added in an amount of 150 cc. Otherwise, ferrite powder was produced in the same manner as in Example 1. The granules obtained in the main assembly process had a volume average particle size of 50.55 μm and a carbon (C) content of 0.0743 mass%.

[0091] [Example 4]

[0092] In the main assembly process, an ammonium polycarboxylate salt was added to the slurry at a ratio of 10 cc per 25 kg of solid content in the slurry, and a 10 mass% aqueous solution of polyvinyl alcohol (PVA) was further added in an amount of 300 cc. Otherwise, ferrite powder was produced in the same manner as in Example 1. The granules obtained in the main assembly process had a volume average particle size of 50.70 μm and a carbon (C) content of 0.0941 mass%.

[0093] [Example 5 (Comparison)]

[0094] In the main assembly process, an ammonium polycarboxylate salt was added to the slurry at a ratio of 10 cc per 25 kg of solid content in the slurry, and a 10 mass% aqueous solution of polyvinyl alcohol (PVA) was further added in an amount of 600 cc. Otherwise, ferrite powder was produced in the same manner as in Example 1. The granules obtained in the main assembly process had a volume average particle size of 51.59 μm and a carbon (C) content of 0.0988 mass%.

[0095] [Example 6 (Comparison)]

[0096] In the raw material mixing process, the raw materials were weighed and mixed so that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn = 14:1. In addition, in the main granulation process, a 10 wt% aqueous solution of polyvinyl alcohol (PVA) was added in an amount of 30 cc without adding a dispersant (ammonium polycarboxylate) to the slurry. Furthermore, the raw material feed rate in the thermal spraying process was set to 2.0 kg / hour. Ferrite powder was produced in the same manner as in Example 1. The granules obtained in the main granulation process had a volume average particle size of 51.17 μm and a carbon (C) content of 0.0561 mass%.

[0097] [Example 7]

[0098] In the raw material mixing process, the raw materials were weighed and mixed so that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn = 14:1. In addition, in the main granulation process, a dispersant (ammonium polycarboxylate salt) was not added to the slurry, and a 10 wt% aqueous solution of polyvinyl alcohol (PVA) was added in an amount of 300 cc. Otherwise, ferrite powder was produced in the same manner as in Example 1. The granules obtained in the main granulation process had a volume average particle size of 50.97 μm and a carbon (C) content of 0.0971 mass%.

[0099] [Example 8]

[0100] In the raw material mixing process, the raw materials were weighed and mixed so that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn = 3:1. In addition, in the main granulation process, a 10 wt% aqueous solution of polyvinyl alcohol (PVA) was added in an amount of 30 cc without adding a dispersant (ammonium polycarboxylate) to the slurry. Ferrite powder was produced in the same manner as in Example 1. The granules obtained in the main granulation process had a volume average particle size of 51.45 μm and a carbon (C) content of 0.0256 mass%.

[0101] [Example 9 (Comparison)]

[0102] In the raw material mixing process, the raw materials were weighed and mixed so that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn = 2.5:1. In addition, in the main granulation process, an ammonium polycarboxylate salt was added to the slurry at a ratio of 10 cc per 25 kg of solid content in the slurry. Ferrite powder was produced in the same manner as in Example 1. The granules obtained in the main granulation process had a volume average particle size of 50.54 μm and a carbon (C) content of 0.0549 mass%.

[0103] [Example 10 (Comparison)]

[0104] In the raw material mixing process, the raw materials were weighed and mixed so that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn = 2:1. In addition, in the main granulation process, an ammonium polycarboxylate salt was added to the slurry at a ratio of 10 cc per 25 kg of solid content in the slurry. Otherwise, ferrite powder was produced in the same manner as in Example 1. The granules obtained in the main granulation process had a volume average particle size of 51.69 μm and a carbon (C) content of 0.0539 mass%.

[0105] [Example 11 (Comparison)]

[0106] In the raw material mixing process, the raw materials were weighed and mixed so that the molar ratio of iron (Fe) to manganese (Mn) was Fe:Mn = 1:0. In addition, in the main granulation process, an ammonium polycarboxylate salt was added to the slurry at a ratio of 10 cc per 25 kg of solid content in the slurry, and a 10 wt% aqueous solution of polyvinyl alcohol (PVA) was further added in an amount of 50 cc. Ferrite powder was produced in the same manner as in Example 1. The granules obtained in the main granulation process had a volume average particle size of 51.28 μm and a carbon (C) content of 0.0552 mass%.

[0107] [Example 12 (Comparison)]

[0108] In the main granulation process, an ammonium polycarboxylate salt was added to the slurry at a ratio of 60 cc per 25 kg of solid content in the slurry, and a 10 wt% aqueous solution of polyvinyl alcohol (PVA) was further added at a ratio of 50 cc. In addition, the mesh size of the sieve used to remove coarse powder in the classification process after thermal spraying was changed, and fine powder was removed using the sieve. Ferrite powder was produced in the same manner as in Example 1. The granules obtained in the main granulation process had a volume average particle size of 51.84 μm and a carbon (C) content of 0.0575 mass%.

[0109] [Example 13 (Comparison)]

[0110] In the thermal spraying process, particles were recovered by a bag filter to obtain the sprayed material. Additionally, in the classification process, coarse powder was removed from the sprayed material by air stream classification, but fine powder was not removed. Otherwise, ferrite powder was produced in the same manner as in Example 12. The granulated material obtained in the main granulation process had a volume average particle size of 51.84 μm and a carbon (C) content of 0.0575 mass%.

[0111] [Example 14]

[0112] In the classification process after thermal spraying, coarse and fine powders were removed from the sprayed material by air stream classification. Otherwise, ferrite powder was produced in the same manner as in Example 12. The granulated material obtained in the main granulation process had a volume average particle size of 51.84 μm and a carbon (C) content of 0.0575 mass%.

[0113] [Example 15]

[0114] The mesh size of the sieve used to remove coarse powder in the classification process after thermal spraying was changed again. Otherwise, ferrite powder was produced in the same manner as in Example 12. The granules obtained in the main granulation process had a volume average particle size of 51.84 μm and a carbon (C) content of 0.0575 mass%.

[0115] (2) Evaluation of ferrite powder

[0116] The following evaluations were performed on the ferrite powders of Examples 1 to 15.

[0117] <Component Analysis - Metal Content>

[0118] The metal content of the ferrite powder was determined by chemical analysis (ICP). First, 0.2 g of the sample (ferrite powder) was weighed, and 60 ml of pure water, 20 ml of 1N hydrochloric acid, and 20 ml of 1N nitric acid were added to it and heated to prepare an aqueous solution in which the sample was completely dissolved. The obtained aqueous solution was set up in an ICP analyzer (Shimadzu Corporation, ICPS-10001V) to measure the metal content.

[0119] <Component Analysis - Carbon Content>

[0120] The carbon content of the ferrite powder was measured using the infrared absorption method. Specifically, 1g of ferrite powder was burned in an oxygen stream to convert the carbon contained in the ferrite powder into carbon dioxide. The amount of infrared absorption of carbon dioxide was measured using an infrared absorption detector (LECO Japan Co., Ltd., Carbon Sulfur Analyzer CS200 type), and the carbon content was calculated from this amount of absorption.

[0121] <Component Analysis - Residual Carbon Compounds>

[0122] Residual carbon compounds in the ferrite powder were analyzed using a high-resolution mass spectrometer (GC / MS). Specifically, 5 g of ferrite powder was weighed and placed in a 200 ml beaker, 500 ml of methyl ethyl ketone (MEK) was added, and ultrasonic treatment was performed for 5 minutes to extract organic components associated with the ferrite powder. The extracted MEK solution was filtered, and the obtained filtrate was used as the test solution. The analysis conditions for the high-resolution mass spectrometer (GC / MS) are shown below.

[0123] - Gas Chromatography: Agilent Technologies, 6890N

[0124] - Mass spectrometer: Agilent Technologies, 5973N

[0125] - Column: Agilent Technologies, DB-5MS (film thickness 0.25㎛)

[0126] - Heating Introductory Unit: Parkin Elmer, TurboMatrix 650ATD

[0127] - Temperature conditions: 50℃ (2 min) to 280℃ (18 min)

[0128] - Heating rate: 20℃ / min

[0129] - Carrier gas flow rate: Helium 1 ml / min

[0130] - Injection method: Splitless 0.5 minutes

[0131] - Inlet temperature: 280℃

[0132] - Interface: 280℃

[0133] - Measured mass range: m / z 29–600

[0134] - Injection volume: 1 µl

[0135] Based on the obtained analysis results, carbon compounds were identified. Identification was carried out as follows. Using an analysis device (Agilent Technologies, 5973N), detection peaks originating from the device and MEK were excluded from the TIC chromatogram, and a library search was performed on each of the remaining detection peaks. The compound with the highest library match rate in the mass spectrum pattern was identified as the residual carbon compound of the ferrite powder.

[0136] <Crystal Form>

[0137] Ferrite powder was analyzed by X-ray diffraction to identify the crystalline phases within the powder. The content ratios of the spinel phase (Fe3O4, MnO·Fe2O3) and the α-Fe2O3 phase were determined. The analysis conditions are as shown below.

[0138] - X-ray diffraction device: Panalytical X'pert MPD (including high-speed detector)

[0139] - Seaman: Co-Kα

[0140] - Tube voltage: 45kV

[0141] - Tube current: 40mA

[0142] - Scan speed: 0.002° / sec (continuous scan)

[0143] - Scan range (2θ): 15–90°

[0144] In addition, the analysis results were interpreted to determine the content ratio of the spinel phase (Fe3O4, MnO·Fe2O3, etc.) and the α-Fe2O3 phase among the crystalline phases of the ferrite powder. The analysis was performed as follows. Specifically, analysis software (HighScore Plus 3.0, manufactured by Panalytical) was used to remove background and Co-Kβ line peaks, and then the peaks of the profile were automatically detected. For each detected peak, the full width at half maximum and position were optimized (refined) using Rietveld analysis, and the content ratio of the spinel phase and the α-Fe2O3 phase was calculated based on the obtained results.

[0145] <Particle Size Distribution>

[0146] The particle size distribution of ferrite powder was measured. First, 10 g of the sample and 80 ml of water were placed in a 100 ml beaker, and two drops of sodium hexametaphosphate were added as a dispersant. Subsequently, dispersion was performed using an ultrasonic homogenizer (SMT, Inc., UH-150 type). At this time, the output level of the ultrasonic homogenizer was set to 4, and dispersion was performed for 20 seconds. Afterward, the bubbles formed on the surface of the beaker were removed, and the sample was introduced into a laser diffraction particle size distribution measuring device (Shimadzu Corporation, SALD-7500 nano) to perform measurements. Through this measurement, the 10% diameter (D10), 50% diameter (volume average particle diameter, D50), 90% diameter (D90), and maximum diameter (Dmax) in the volumetric particle size distribution were determined. The measurement conditions were set to pump speed 7, built-in ultrasonic irradiation time 30, and refractive index 1.70-0.50i.

[0147] <BET Specific Surface Area>

[0148] The BET specific surface area of ​​the ferrite powder was measured using a specific surface area measuring device (Macsorb HM model-1208, Mountech Co., Ltd.). First, about 10 g of the obtained ferrite powder was placed on weighing paper and degassed using a vacuum dryer, confirming that the vacuum level was -0.1 MPa or lower. Subsequently, moisture attached to the surface of the particles was removed by heating at 200°C for 2 hours. About 0.5 to 4 g of the moisture-removed ferrite powder was placed into a standard sample cell dedicated to the measuring device and accurately weighed using a precision balance. Next, the weighed ferrite particles were set into the measuring port of the measuring device, and measurements were performed. The measurement was performed using the single-point method. The measurement atmosphere was set to a temperature of 10 to 30°C and a relative humidity of 20 to 80% (no condensation).

[0149] <Tap Density>

[0150] The tap density of the ferrite powder was measured in accordance with JIS Z 2512-2012 using a USP tap density measuring device (Hosokawa Micron Co., Ltd., Powder Tester PT-X).

[0151] <Shape Factor (SF-1)>

[0152] The average shape factor (SF-1) of the ferrite powder was calculated as follows. The ferrite powder was analyzed using a particle image analyzer (Malvern Panalytical, Morphology G3). During the analysis, image analysis was performed on each of the 30,000 particles in the powder, and the maximum length (horizontal ferrite diameter) R (unit: μm), projected perimeter L (unit: μm), and projected area S (unit: μm) were calculated. 2 ) was automatically measured. Next, SF-1 for each particle was calculated according to the following formula (1), and the average value was taken as the SF-1 of the ferrite powder.

[0153]

[0154] <Magnetic Properties - Saturation Magnetization, Residual Magnetization, and Coercivity>

[0155] The magnetic properties (saturation magnetization, remanent magnetization, and coercivity) of ferrite powder were measured as follows. First, a sample was filled into a cell with an inner diameter of 5 mm and a height of 2 mm and set up in a vibrating sample type magnetic measuring device (Toei Industry Co., Ltd., VSM-C7-10A). An applied magnetic field was applied and swept to 5 kOe, and then the applied magnetic field was reduced to draw a hysteresis curve. From the data of the drawn curve, the saturation magnetization (σs), remanent magnetization (σr), and coercivity (Hc) of the sample were determined.

[0156] <Self-Characteristics - Indirectness>

[0157] The permeability of ferrite powder was measured using an RF impedance / material analyzer (Agilent Technologies, Inc., E4991A) and a magnetic material measuring electrode (16454A). First, 9g of ferrite powder and 1g of binder resin (Kynar301F: polyvinylidene fluoride) were placed in a polyethylene container (capacity 100ml), and stirring and mixing were performed using a ball mill at a rotation speed of 100 rpm. Approximately 0.6g of the obtained mixture was filled into a die (inner diameter 4.5mm, outer diameter 13mm), and a molded body was formed by applying pressure of 40 MPa for 1 minute using a press machine. The obtained molded body was heat-cured at 140°C for 2 hours using a hot air dryer to be prepared as a sample for measurement. The obtained measurement sample was set in an RF impedance / material analyzer, and the outer diameter, inner diameter, and height of the measurement sample, which had been measured in advance, were input. Measurements were performed by sweeping a logarithmic scale over a range of 100 mV amplitude and a measurement frequency of 1 MHz to 3 GHz. The real part (μ') and imaginary part (μ'') of the complex permeability at a frequency of 100 MHz were obtained, and the loss coefficient (tanδ) was calculated according to the following equation (5).

[0158]

[0159] <Electrical Characteristics - Volume Resistance>

[0160] The volume resistivity of ferrite powder was measured using a Teflon (registered trademark) container (inner diameter 17.6 mm) with an electrode attached to the bottom edge and an upper electrode. First, ferrite powder was placed into the container and pressurized so that the height at the time of measurement was 4 mm, and an electrode was attached to the top. The measurement was performed with a load of 1 kg applied to the upper electrode, and the current flowing was measured using an insulation resistance meter (Keithley Instruments, 6517A) while increasing the voltage stepwise up to 1000 V at 5-second intervals every 50 V. The relationship between the current and the applied voltage under a voltage of 100 V was determined, and the volume resistivity was calculated from this.

[0161] <Electrical Characteristics - Breakdown Voltage>

[0162] When measuring volume resistance, the applied voltage just before exceeding the output current of the measuring device (insulation resistance meter) of 20mA was determined, and this applied voltage was set as the breakdown voltage (VBD).

[0163] <Resin Curing Performance - Viscosity>

[0164] Ferrite powder was applied to the resin composition, and the viscosity of the resin composition was measured. First, 70 parts by mass of ferrite powder, 27 parts by mass of the main component (epoxy resin), and 3 parts by weight of the curing agent were dispersed and mixed using a rotating-orbit type mixer to prepare a resin composition. For the obtained resin, the viscosity immediately after preparation and the viscosity after 5 seconds were measured using a Type B viscometer. Meanwhile, since Example 5 had low volume resistivity, the resin curing performance was not evaluated.

[0165] <Resin Curing Performance - Curing Time>

[0166] The obtained resin composition was dried under conditions of 120°C × 5 minutes. The resin composition after drying was heated at 180°C to promote curing, and the curing time at which the degree of resin curing reached 95% or more was determined. Based on the determined curing time, grades were established as follows.

[0167] A: Curing time is std×1.00 or greater and std×2.00 less than

[0168] B: Curing time is std×2.00 or greater and std×3.00 less than

[0169] Here, the degree of resin curing refers to the extent of progress (reaction rate) of the resin curing reaction. The degree of resin curing of the unreacted material is 0%, and the degree of resin curing of the reacted material is 100%. The degree of resin curing was determined using an FT-IR (Fourier Transform Infrared Spectroscopy) device. Specifically, infrared rays were irradiated onto the resin to obtain an FT-IR spectrum by transmitting or spectrally analyzing the light, and the progress of the resin curing reaction was analyzed using this spectrum. Then, the degree of resin curing was determined by comparing the spectra of the unreacted material, the material after 100% reaction, and the resin to be measured, and comparing the peak intensity of each sample in the region showing the greatest difference. The curing time of each sample was calculated using the curing time of Example 1 as the standard (std).

[0170] (3) Result

[0171] The results of the evaluation for Examples 1 to 15 are shown in Tables 2 and 3. Examples 1 to 4, Example 7, Example 8, Example 14, and Example 15 are example samples, and Examples 5, Example 6, and Examples 9 to 13 are comparative example samples.

[0172] As shown in Tables 2 and 3, the ferrite powder of all samples consisted of spherical particles. However, Comparative Example 5 had ferrite powder that did not contain α-Fe2O3, and as a result, had low volume resistivity and breakdown voltage, which was problematic in terms of breakdown voltage.

[0173] Meanwhile, comparative examples 6, 11, and 13 had an excess amount of α-Fe2O3, and as a result, the saturation magnetization (σs) was low. Furthermore, Example 13 had a problem in that the volume average particle size was small and the viscosity of the resin composition was too high, as well as poor resin curing performance. Comparative examples 9 to 11 had iron (Fe) content and / or manganese (Mn) content of the ferrite powder outside the range of the present embodiment, and as a result, there were problems in terms of magnetic properties (saturation magnetization, permeability, loss factor). In particular, Example 11, which contained almost no manganese (Mn) and had an excess amount of α-Fe2O3, had a low saturation magnetization (σs) and a high coercivity (Hc), which resulted in a small real part of permeability (μ') and an increased loss factor (tanδ). Comparative example 12 had a problem in that the volume average particle diameter (D50) was excessively large, so the loss factor (tanδ) was high and the breakdown voltage was low.

[0174] In this regard, Examples 1 to 4, 7, 8, 14, and 15 were not only excellent in terms of magnetic properties (saturation magnetization, coercivity, permeability, loss factor), but also had high volume resistivity and breakdown voltage. In particular, Examples 1 to 3, 8, and 14 did not undergo breakdown during measurement and were very excellent in terms of breakdown voltage. In addition, Examples 1 to 4, 7, 8, and 15 had low viscosity when ferrite powder was applied to the resin composition. For this reason, it was found that they are very suitable for application to resin compositions with a high filler rate.

[0175]

[0176]

[0177]

Claims

Claim 1 A ferrite powder composed of spherical ferrite particles, wherein the ferrite powder contains 55.0 to 70.0 mass% of iron (Fe) and 3.5 to 18.5 mass% of manganese (Mn), and the amount of α-Fe2O3 is greater than 0.0 mass% and less than or equal to 7.5 mass%, wherein the ferrite powder contains 1.0 mass% or less of other components other than iron (Fe), manganese (Mn), and oxygen (O), the volume average particle diameter (D50) of the ferrite powder is 15.0 μm or less, and the average shape factor SF-1 of the ferrite powder is 100 to 110. Claim 2 A ferrite powder according to claim 1, wherein the amount of α-Fe2O3 is 3.0 mass% or more and 6.0 mass% or less. Claim 3 In claim 1, the ferrite powder having a volume average particle diameter (D50) of 2.0 μm or more. Claim 4 delete Claim 5 A ferrite powder according to claim 1, wherein the carbon (C) content of the ferrite powder is 0.12 mass% or less. Claim 6 In claim 1, the volume resistivity of the ferrite powder is 1.0 × 10 8 Ferrite powder with a Ω·cm or greater. Claim 7 A method for manufacturing ferrite powder as described in any one of claims 1 to 3, 5 and 6, comprising: a process of mixing ferrite raw materials to produce a raw material mixture; a process of plasticizing the raw material mixture to form a plasticized product; a process of crushing and granulating the plasticized product to form a granulated product; and a process of spraying the granulated product to form a sprayed product, wherein the carbon content of the granulated product is 0.001 to 0.095 mass%, and in the spraying process, the raw material supply rate is 2.5 to 9.0 kg / hour, the combustion gas flow rate is 3 to 10 m³ / hour, and the oxygen flow rate is 18 to 60 m³ / hour.

Citation Information

Patent Citations

  • Mangan zinc ferrite resintering process

    CN102010192A

  • Mn ferrite powder, resin composition, electromagnetic wave shielding material, electronic material, and electronic component

    WO2019159797A1